Effectiveness of Participatory Extension on Farmers' Knowledge, Attitude, and Skills in Using Beauveria bassiana for Rice Bug Control - Eny Wahyuning Purwanti; Himmata Suryanit; Suryaman Sule (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2026)
This study aimed to determine the effectiveness of a participatory extension approach in promoting the utilization of the entomopathogenic fungus Beauveria bassiana as a biological control agent for rice bug infestation in rice fields. A quasi-experimental design with pretest-posttest measurement was employed, utilizing participatory action research methodology. The participatory extension process involved the identification of local potential, collaborative planning with farmers, and farmer-inclusive evaluation, utilizing the POAC (Planning, Organizing, Actuating, Controlling) management cycle. The intervention targeted members of the Rukun Tani Farmer Group, with extension materials sourced from literature review and applied research. The